Penerapan sistem akuntansi keuangan daerah pada Badan Perencanaan Penelitian dan Pengembangan di Kabupaten Minahasa Selatan - Tumbel, Jinnyfer; Pangemanan, Sifrid; Alexander, Stanly (Universitas Sam Ratulangi, 2019)
Genaral demand for accountability is one of the factor that driven the development of public sector accounting in Indonesia. Government Regulation No. 71 of 2010 concerning Government Accounting Standards explains that government financial reports must provide information that is useful for users. Quality financial reports require an adequate regional financial accounting system, because the system is supporting the creation of transparent and accountable regional financial management. Through the application of the regional financial accounting system, it is expected to be able to carry out its duties and functions so that Good Governance is created. This study used descriptive qualitative research that aims to reveal qualitative information so that it emphasizes the application of regional financial accounting systems and implemented interviews and documentation for getting the data. The results of this study indicate that the application of the regional financial accounting system is in accordance with applicable regulations.